ANALISIS PENGARUH PERBEDAAN TINGKAT INFLASI DAN PERBEDAAN SUKU BUNGA INDONESIA â US TERHADAP PERGERAKAN NILAI TUKAR RUPIAH PERIODE 2000:1 â 2012:2 - , FLORA SUSANTI P ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to empirically examine the influence of interest rate differential and inflation rate differential on exchange rate changes based on the Purchasing Power Parity Theory (PPP) and International Fisher Effect Theory (IFE) in Indonesia. To test these theory, researcher use quarterly data from 2000 quarter 1 until 2012 quarter 2. Regression results show that interest rate differential and inflation rate differential have a long run relationship on exchange rate changes. Bound Testing is used to test this cointegration. To estimate short run relationship within model, researcher applies Error Correction Model (ECM) â Dynamic approach. This estimation show that interest rate differensial and inflation rate differential have negative significant influence on changes in exchange rate. Those results also indicate that, overall, the changes of exchange rate conform to Purchasing Power Parity Theory (PPP) and International Fisher Effect Theory (IFE).